Prevention of Theft with Aggravated Circumstances at Semarang City - Rochmad, Rochmad; Bramasta, Raden Ariel Andro (Indonesian Journal of Advocacy and Legal Services, 2023)
The operational task of the police is a duty directly related to the community, and the benchmark for its success is the establishment of public trust in the Indonesian National Police (Polri). In the jurisdiction of the Semarang Metropolitan Police (Polrestabes Semarang), there is still a prevalence of aggravated theft crimes. Many people suffer losses due to the frequent occurrence of such criminal acts, including physical harm, economic losses, and psychological disturbances. The implementation of motor vehicle patrols by the Satuan Samapta (Security and Order Maintenance Unit) and the factors influencing the activities of the Satuan Samapta motor vehicle patrols in preventing aggravated theft crimes need to be optimized. Management theory, crime prevention theory, organizational resource theory, patrol concepts, and the concept of aggravated theft crimes are applied to enhance the effectiveness and efficiency of the Satuan Samapta motor vehicle patrol implementation. The Satuan Samapta patrols still face various obstacles from internal and external factors within the unit, thus requiring organizational resources to support the success of patrol implementation.